Suppression of channel conductance by diacetyl monoxime in guinea pig and embryonic chick cardiomyocytes - Sada Hideaki; Ban Takashi; Sperelakis Nicholas (Acta Pharmacologica Sinica, 2016)
AIM: To examine the effects of diacetyl monoxime (DAM), and putative dephospohrylating agent, on conductance of the cardiac Ca, Na, and K channels. METHODS: The Ca (ICa), Na (INa), and K (IK) currents were recorded in single ventricular myocytes from guinea pigs and chick embryos before and after addition of DAM using the whole-cell voltage-clamp technique. RESULTS: DAM 10 mmol.L-1 reduced rapidly the amplitudes of ICa (by about 30%), INa (by about 25%), and IK (by 25%-50%) without alterations of the voltage-dependence. CONCLUSION: DAM was a channel inhibitor of the unique type having nonselective phosphatase activities.